(untitled) (Živi jezici: Journal for Foreign Languages and Literatures, 2017)
Modern language teaching aims to improve all language competencies so that the candidate becomes a successful and independent user of the target language. Although these ideas are present at different levels of language education, the results of this qualitative research, conducted during the reform of study programs at the Faculty of Philology in Belgrade, indicate that there is not always an essential understanding of these principles, which sometimes leads to their contradictory interpretation. Namely, it is not enough for lecturers and students to be acquainted with modern trends in language science because it does not affect the change of their approach to teaching, ie language learning. It is crucial to create conditions for participants to reconsider their deep beliefs and attitudes about education, in order to fundamentally change their actions.